BLENDED LEARNING AS A TOOL FOR DEVELOPING STUDENTS' DIGITAL COMPETENCE (Web of Technology: Multidimensional Research Journal, 2024)
The article discusses the use of the blended learning model for developing the digital competence of students in engineering and pedagogical fields. An overview of the concept of digital competence and its importance in the context of digitalization of education is presented. A methodology based on the use of the DigitalSkills platform is described, which contributes to the development of key digital skills of students when completing independent tasks of varying levels of complexity. The results of the study are presented, demonstrating high student satisfaction with the platform functionality and its potential in the educational process. A conclusion is made about the importance of implementing adaptive digital technologies to improve the quality of training specialists in the context of the digital transformation of society.